The Pterygopalatine Fossa - Robert Acland; Nicole Herring; Jennifer Brueckner-Collins (Association of American Medical Colleges, 2012)
Abstract Introduction The pterygopalatine fossa is a relatively inaccessible location that lies in the deep face and thus, is a traditionally difficult area for health science students to conceptualize and comprehend. Clinically, it is an important region with several inputs (distal maxillary artery, nerve of the pterygoid canal (vidian nerve), and maxillary division of the trigeminal nerve), as well as a multitude of outputs. Because it is a fat-filled area with no fascial boundaries and many communications to adjacent spaces, the pterygopalatine fossa serves as an important route for the spread of disease, as well as a key clinical setting for epistaxis and trauma. This videographic tutorial provides a unique anatomical perspective of the pterygopalatine fossa, using a Stortz™ 4mm straight endoscope, attached to a high definition camera. Methods This tutorial elucidates the bony anatomy of this fossa from within its depths, demystifying its complexity for health science students in a 4.5 minute-long narrated video. Pre- and posttests are included for students to evaluate their mastery of this topic. Results This product has been reviewed and evaluated by first-year medical students from the Class of 2015 at the University of Louisville. Students recommended that the product be incorporated into the curriculum on an annual basis. Students commented that the anatomical views and dissections provided were unique from any other material in their standard curriculum. They also cited the narration, summary, and overall organization as strengths of the program. Discussion The pterygopalatine fossa has traditionally been a difficult area for students to conceptualize, due to its deep placement in the skull. This resource provides health science students a visual guide to assist in their understanding of this anatomical component.